1994
DOI: 10.1080/00223980.1994.9712750
|View full text |Cite
|
Sign up to set email alerts
|

Self-Discrepancies and Perceived Peer Acceptance

Abstract: We examined developmental changes in the self and the relationship between such changes and perceived peer acceptance in a sample of 414 6- to 11-year-old Australian children (211 boys, 203 girls) who completed a self-discrepancy scale and a perceived peer acceptance scale specifically constructed for this study. Resulting scores suggested that critical periods in developmental changes in the structure of the self occur at about 7 to 8 years and that a relationship exists between the reporting of a comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This differentiation has been noted from as early as five years (Ittyerah & Mahindra, 1990;Sanders & Harper, 1976). There is also related evidence of gender differentiation in the case of self-discrepancy, with Brown and Kafer (1994) reporting more self-discrepancies, of a larger magnitude, for six-year-old boys than for girls. This study is the only one of three recently published that considered gender and self-discrepancy in middle childhood; the other two studies investigated populations of undergraduate university students (Gardner & Tockerman, 1993;Strauman et al, 1991).…”
Section: Place Of Residencementioning
confidence: 82%
See 3 more Smart Citations
“…This differentiation has been noted from as early as five years (Ittyerah & Mahindra, 1990;Sanders & Harper, 1976). There is also related evidence of gender differentiation in the case of self-discrepancy, with Brown and Kafer (1994) reporting more self-discrepancies, of a larger magnitude, for six-year-old boys than for girls. This study is the only one of three recently published that considered gender and self-discrepancy in middle childhood; the other two studies investigated populations of undergraduate university students (Gardner & Tockerman, 1993;Strauman et al, 1991).…”
Section: Place Of Residencementioning
confidence: 82%
“…In the first phase, administration of the instruments was done over four separate sittings. The Piers-Harris Children's Self-Concept Scales (1984); (P-H) and the Self-Discrepancy Questionnaire (Brown & Kafer, 1994); (SDQ) were administered to each class. The Chandler Story Task (1973); (CST) and the Peabody Picture Vocabulary Test-Revised (Dunn & Dunn, 1981); (PPVT-R) were administered to each student individually in an interview room away from the classroom.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown and Kafer (1994) found that there was a dramatic increase in self-awareness around age 7 or 8. The kindergarteners in our sample were reporting perceived acceptance prior to this time, resulting in a greater range in the extent to which children’s perceptions correlated with peer nominations.…”
Section: Discussionmentioning
confidence: 96%